Biosynthesis of Silver Nanoparticles by Escherichia coli - Ghorbani, H.R. (Asian Journal of Chemistry, 2012)
Development of reliable and eco-friendly processes for synthesis of metallic nanoparticles is an important step in nanotechnology. One of the options to achieve this objective is to use natural factories such as biological systems. In this study, we have investigated the synthesis of nanoparticles of silver by reduction of aqueous Ag+ ions with the culture supernatant of Escherichia coli (DH5a). UV-visible spectrum of the aqueous medium containing silver ion showed a peak at 415 nm corresponding to the plasmon absorbance of silver nanoparticles. The silver nanoparticle were 10-100 nm in dimensions as measured by TEM images. The process of reduction is extracellular, which makes it an easier method for the synthesis of silver nanoparticles.